Procedure and Legal Consequence Due to the Conversion of Commanditaire Venotschap to Limited Liability Company - Ang Vincent Lawrence Angelo Sendow (Fakultas Hukum Universitas Hang Tuah, 2018)
The company takes an important part of the social life of the community. In order to carry out its business activities, the parties granted the freedom to conduct business individually or through a business entity. One form of business entity that is still alive which is oftenly used is through a Commanditaire Vennotschap (CV). As the time goes by, the existence of the CV is deemed no longer able to meet the demands arising from the development. This triggered the desire of the parties to change the form of business from CV into a legal entity. Limited Liability Company or in Indonesia called as “Perseroan Terbatas (PT)” becomes the main choice by the entrepreneurs. The conversion of a CV into a PT is a step that can be taken by the entrepreneurs. The conversion of the CV into a PT is possible to be carried out without having to terminate the CV in advance as the termination of the CV will have impacts on the agreement it has made to be settled on that time, whereas on the other hand the agreements that have been made have not yet expired or done.